A gastronomia e o turismo: a panificação tradicional e a gormetização na região de São Gotardo, Caxias do Sul, RS - Johannsen, Etiene Meyer (My University, 2018)
The main objective of this research is to analyze traditional bakery processes, associated to the Italian influence in São Gotardo, in the district of Vila Seca, Caxias do Sul-RS, as well as its possible contribution to local tourism. Thus, the aim of this research is to rescue the gastronomic memory, based on the questioning of knowledge and practices that, in the community memory, are associated to traditional bread making in São Gotardo and, if they are rescued, they can be consolidated to reintegration in the community’s daily lives, qualifying its gastronomy, considering local tourism. This is a participative research, that was carried out through interviews, photographical records, notes in research diary, as well as bakery workshops. Bakery workshops were structured, to stimulate the people interviewed to talk about their knowledge and practices associated to bakery, and the introduction to gourmet techniques. We concluded that from the technique inherent to baking and it is possible to increase flavors and formulation, without losing the local identity.
A presente pesquisa objetiva analisar os processos de panificação tradicional associados à italianidade em São Gotardo, no distrito de Vila Seca, Caxias do Sul, RS, e sua possível contribuição ao turismo no local. Esta pesquisa busca, portanto, registrar a memória gastronômica, a partir do questionamento sobre quais os saberes e fazeres que, nas memórias da comunidade, estão associados à panificação tradicional em São Gotardo e que, se forem mantidos ativos e consolidados nas práticas gastronômicas locais, coloquem-se como opção no âmbito do turismo local. A metodologia teve como suporte a pesquisa participativa, com entrevista, registro fotográfico e anotações em diário de pesquisa, além da realização de oficinas de panificação. As oficinas de panificação foram estruturadas para instigar os comentários sobre os saberes e fazeres associados ao pão, assim como para introdução de técnicas de gourmetização. Concluiu-se que a partir de técnica inerente à panificação é possível incrementar sabores e formulação, sem que se perca a identidade local.
Keywords: Gastronomia; Turismo; Panificação; Caxias do Sul (RS); Gastronomy; Tourism; Bread industry; Caxias do Sul (Brazil)